Trash streams as a manifestation of youth subculture - S. A. Grishaeva; N. N. Pushkareva (Цифровая социология)
Young people are always looking for an opportunity to express and to find themselves, to their find place in this world, including through subcultures. However, sometimes these subcultures become countercultures, that is, they carry values that contradict the dominant culture of society. Modern youth spends a significant part of their time on the Internet, and trash streams are one of the types of Internet leisure. The purpose of this article is to clarify what such a subcultural phenomenon as trash streams is, how they are evaluated by young people and representatives of the older generation. In the course of the study, four focus groups and two project sessions were conducted with schoolchildren and students, as well as an online survey of 8,942 respondents of various age categories. The vast majority of respondents, regardless of age, believe that it is necessary to prohibit or at least limit the broadcast of trash streams. Nevertheless, there is a fairly significant part of respondents who believe that “people voluntarily participate in trash streams, this is their right, and the ban will only increase demand. The respondents’ opinions also differ when answering the following questions: “Do trash streams have customers?”, “Are trash streams dangerous or not?”. At the same time, the vast majority of respondents do not consider personal participation in trash streams for themselves.